2015
DOI: 10.1039/c5ra09150k
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar Zn(ii) sensing and subsequent PPi detection in physiological medium and live cells with a benzothiazole functionalized chemosensor

Abstract: Graphical AbstractNanomolar Zinc detection and subsequent pyrophosphate sensing in physiological medium using a benzothiazole modified conjugated ligand and their application in paper strip and live cell imaging is demonstrated.New fluorescent chemosensor (L1) exhibit relay recognition of Zn 2+ and pyrophosphate anion in mixed buffer solution at physiological pH. The probe exhibit excellent Zn 2+ induced turn-on fluorescence, even as low as 1 nM (LOD = 71 ppb). Further, addition of pyrophosphate ion led to que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…On the other hand, the vibrations of the cyclic‐N of benzothiazole moiety remain almost unchanged, revealing that the ligand is coordinated to the Cu (II) center in a neutral bidentate manner (N, O) through the azomethine‐N and lactone carbonyl‐O atoms 44–46 . In the FT‐IR spectrum of the Zn (II) complex ( 2 ) and there is a considerable shift to higher wavenumber of both the azomethine and benzothiazole nitrogen vibrations, while the lactone carbonyl and NH bands remain unaltered, indicating the that the ligand coordinates to the Zn (II) center in a neutral bidentate manner (Figure 1()) through both of the azomethine nitrogen atoms 45, 47–49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the vibrations of the cyclic‐N of benzothiazole moiety remain almost unchanged, revealing that the ligand is coordinated to the Cu (II) center in a neutral bidentate manner (N, O) through the azomethine‐N and lactone carbonyl‐O atoms 44–46 . In the FT‐IR spectrum of the Zn (II) complex ( 2 ) and there is a considerable shift to higher wavenumber of both the azomethine and benzothiazole nitrogen vibrations, while the lactone carbonyl and NH bands remain unaltered, indicating the that the ligand coordinates to the Zn (II) center in a neutral bidentate manner (Figure 1()) through both of the azomethine nitrogen atoms 45, 47–49 …”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46] In the FT-IR spectrum of the Zn (II) complex (2) and there is a considerable shift to higher wavenumber of both the azomethine and benzothiazole nitrogen vibrations, while the lactone carbonyl and NH bands remain unaltered, indicating the that the ligand coordinates to the Zn (II) center in a neutral bidentate manner (Figure 1(2)) through both of the azomethine nitrogen atoms. 45,[47][48][49] In the FT-IR spectrum of the Pd (II) complex (3), the ligand behaves in a mono-negative bidentate manner (N, N-donor) as the NH band disappears upon coordination together with the appearance of a new azomethine group vibration at 1650 cm −1 and no a significant change in lactone carbonyl band (Figure 13 53,54 The neutral monodentate bonding (N-donor) is present in the Ag(I) complex (5) (Figure 1(5)) since only the cyclic nitrogen mode undergoes a significant shift to lower wavenumber. 55 The coordination of the bidentate nitrato ion is indicated by the presence of three bands due to ν(N=O) at 1480 cm −1 , ν as (NO 2 ) at 1295 cm −1 and ν s (NO 2 ) at 1018 cm −1 and since the separation of the two highest bands is 185 cm −1.56, 57 The hydrazide ν(N-N) band that resides at 1057 cm −1 shifts to higher wavenumber supporting azomethine-N coordination.…”
Section: Vibrational Spectramentioning
confidence: 99%
“…Gogoi et al [150] have reported a novel benzothiazole containing Schiff base 49 which rendered relay recognition of Zn 2 + and ppi in physiological medium (Scheme 51). The Zn 2 + sensing wasevidenced in mixed buffered medium and also in the physiological medium in presence of HSA, BSA and SBF.…”
Section: Detection Of Pyrophosphates and H 2 Pomentioning
confidence: 99%
“…Gogoi et al . have reported a novel benzothiazole containing Schiff base 49 which rendered relay recognition of Zn 2+ and ppi in physiological medium ( Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…One phosphate-recognition strategy is the use of metal complexes, mostly involving transition metals, in which the metal ion acts as an anchoring point for the phosphate species. Although different metal ions including transition, lanthanide, and main group metal ions have been used, one of the most commonly used ions for this purpose is Zn 2+ [28,29].…”
Section: Introductionmentioning
confidence: 99%